Buckling and Vibration Estimation of Girder Steel Portal Frames using the Bayesian Updating Methods - Fahmi, Fahmi H.; Al-Zaidee, Salah (Engineering, Technology & Applied Science Research, 2023)
In practice, structural systems are complicated. When dealing with such systems, the use of analytical simulations is or may be impossible to apply, since the problem includes many variables with partial differential formulations. The stability and dynamic response of structures is an important aspect that must be paid particular attention to in order to ensure safety against collapse. A physical phenomenon of a reasonably straight, slender member bending laterally (usually abruptly) from its longitudinal position due to compression is referred to as buckling. Two kinds of buckling can be distinguished: (1) bifurcation-type buckling and (2) deflection-amplification-type buckling. In vibration, frequencies and mode shapes must be known in order to use some methods of dynamic response analysis. To calculate frequencies and modes, an eigenvalue problem is solved in algebraic form. In structural dynamic problems, only the lowermost eigenpairs are of important interest. The highest eigenpairs are not needed and are not accurate due to discretization errors.